Pengaruh Konsentrasi Elektrolit KCl terhadap Produksi Gas Hidrogen - Erwandri, Rianovriani; Zainul, Rahadian (Jurusan Kimia FMIPA UNP, 2019)
Abstract â”€ One of the effective alternative energy to replace fossil fuels is hydrogen gas. Hydrogen gas as a fuel is an alternative energy that is environmentally friendly and does not produce harmful products. To produce hydrogen gas can be done through the method of electrolysis of water, which is to decompose H2O compounds into hydrogen gas and oxygen gas with the help of an electric current. The factors that influences the production of hydrogen gas during the electrolysis process is the concentration of electrolyte solution, so the concentration of the solution (M) becomes an independent variable and the amount of gas concentration (ppm) produced is the dependent variable in this research. As for the variation of electrolyte concentrations used are 0,1 M; 0,25 M; 0,5 M; 0,75 M, and 1 M. the current and voltage used in the electrolysis process are fixed at 6 ampere and 2 volts for 1 hour. This research aims to determine the concentration (ppm) of hydrogen gas produced through the electrolysis process. The concentration of hydrogen gas produced is determined using an MQ-8 sensor. Research results showed that the production of hydrogen gas using aquades electrolytes was 10 ppm for the use of KCl electrolytes with various concentrations respectively was 13 ppm, 17 ppm, 26 ppm, 37, ppm, and 34 ppm. From the research results obtained: the greater the concentration of chloride salt used, the more hydrogen gas in produced and the larger the size of the electrolyte ion, the greater the hydrogen gas produced.